2010
DOI: 10.1111/j.1745-7599.2010.00515.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of an osteoporosis disease‐management program managed by nurse practitioners

Abstract: NPs play an important leadership role in managing osteoporosis within a large health maintenance organization. The screening and interventions used can be applied by any NP in any practice setting on an individual basis to reduce hip fracture rates in the United States.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(29 citation statements)
references
References 23 publications
0
29
0
Order By: Relevance
“…The “4i” Lucky Bone FLS in Montreal, Canada, demonstrated that there was overwhelming consensus between their physicians and the decisions made by their specialist nurses when they were empowered within a system involving an order set to allow them to investigate and manage patients,24 suggesting that such a service can be safely and efficiently run with minimal supervision from physicians 35. In terms of identifying patients at risk of osteoporosis, most services would initiate an assessment in patients over the age of 50 years presenting with a fragility fracture,21,25,26,28 although some centers also included women as young as 40 22. Fragility fractures are those sustained following minimal trauma, eg, fall from a standing height, and those considered typical of osteoporotic fragility fractures 36…”
Section: Models Of Flsmentioning
confidence: 99%
“…The “4i” Lucky Bone FLS in Montreal, Canada, demonstrated that there was overwhelming consensus between their physicians and the decisions made by their specialist nurses when they were empowered within a system involving an order set to allow them to investigate and manage patients,24 suggesting that such a service can be safely and efficiently run with minimal supervision from physicians 35. In terms of identifying patients at risk of osteoporosis, most services would initiate an assessment in patients over the age of 50 years presenting with a fragility fracture,21,25,26,28 although some centers also included women as young as 40 22. Fragility fractures are those sustained following minimal trauma, eg, fall from a standing height, and those considered typical of osteoporotic fragility fractures 36…”
Section: Models Of Flsmentioning
confidence: 99%
“…Other interventions, such as the development of an osteoporosis exemplary-care program that identified, educated, evaluated, referred, and treated patients at risk of fracture through coordination among orthopaedists, a metabolic bone disease clinic, and nuclear medicine, have had more success; a study of 430 Canadians found nearly 96% receive appropriate attention after a fracture [3]. Another model for osteoporosis disease management is the Healthy Bones program of Kaiser Permanente Southern California (Kaiser SCAL), a health maintenance organization (HMO) [9,12]. Kaiser SCAL has an electronic medical records (EMR) system that can track DXA scans, fractures, and medication use.…”
Section: Search Strategy and Criteriamentioning
confidence: 99%
“…The inpatient and outpatient modules of the EMR were used to identify diagnostic codes associated with periprosthetic fractures using the fractures and dual-energy x-ray absorptiometry (DEXA) scan results of members of the KPSC health care system was used to obtain bone mineral density results and verify periprosthetic fractures. Details on this data source and its processes have been published elsewhere [9][10][11].…”
mentioning
confidence: 99%